Molluscs community in Batang Kayan estuary, Lundu, Sarawak - Abang Abdullah., Abang Azizil Fansuri (Universiti Malaysia Sarawak, (UNIMAS), 2011)
The study was designed to determine the molluscs community in mangrove area which included the composition, distribution, zonation and water quality parameters. The survey was conducted in mangrove area at Batang Kayan Estuary, Lundu, Sarawak on October 20 I O. The survey mainly used line transects and quadrate method. The main group of molluscs identified was Gastropods and Bivalve. There a total of eleven families which consist of twenty one species. Along the Batang Kayan there are seven families consist of fourteen species. The first line transect there are five families consist of seven species and the second line transect there are four families consist of 6 species. While for the vertical zonation there are 6 families consist of 6 species. There weak correlation of water quality parameter for Station along Batang Kayan. For line transect, there are strong correlation of hlorophyll a at transect two but weak correlation with total organic matter same with transect one. The might be other factors that dominant in influence the community of molluscs such as types of substrate. Key words: Mangrove area, molluscs community,